PRODUCTION OF JUICES AND SILK SEED CONCENTRATES - Abror Samandarov; Prof. Kuchkor Dodaev; Ass. Dilrabo Maksumova (Galaxy International Interdisciplinary Research Journal, 2021)
The article discusses the prospects for large-scale cultivation and effective use of mulberry fruits. processing at small enterprises and production of juices, their concentrates, dried mulberries, food colors.